The Existence of Local Wisdom Value Through Minangkabau Dance Creation Representation in Present Time - Indrayuda, Indrayuda (Harmonia: Journal of Arts Research and Education, 2016)
This paper is aiming at revealing the existence of local wisdom values in Minangkabau through the representation of Minangkabau dance creation at present time in West Sumatera. The existence of the dance itself gives impact to the continuation of the existence of local value in West Sumatera. The research method was qualitative which was used to analyze local wisdom values in the present time Minangkabu dance creation representation through the touch of reconstruction and acculturation as the local wisdom continuation. Besides, this study employs multidisciplinary study as the approach of the study by implementing the sociology anthropology of dance and the sociology and anthropology of culture. Object of the research was Minangkabau dance creation in present time, while the data was collected through interview and direct observation, as well as documentation. The data was analyzed by following the technique delivered by Miles and Huberman. Research results showed that Minangkabau dance creation was a reconstruction result of the older traditional dance, and through acculturation which contains local wisdom values. The existence of Mianngkabau dance creation can affect the continuation of local wisdom values in Minangkabau society in West Sumatera. The existence of dance creation has maintained the Minangkabau local wisdom values in present time.